2003
DOI: 10.1590/s0104-66322003000400012
|View full text |Cite
|
Sign up to set email alerts
|

Friction losses in valves and fittings for power-law fluids

Abstract: -Data on pressure drop were obtained in stainless steel, sanitary fittings and valves during laminar and turbulent flow of aqueous solutions of sucrose and xanthan gum, which were selected as model fluids. The rheological properties of these solutions were determined and the power-law model provided the best fit for experimental data. Friction losses were measured in fully and partially open butterfly and plug valves, bends and unions. Values of loss coefficients (k f ) were calculated and correlated as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 11 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…Shear rate range was 0.5 to 300 s -1 and both upward and downward tests were performed in duplicate for each temperature and soluble solids content combination. The experimental procedure was previously tested by a rheological study of ethylene glycol and chlorobenzene (Telis-Romero et al, 2005;Polizelli et al, 2003).…”
Section: Density and Rheological Behaviormentioning
confidence: 99%
“…Shear rate range was 0.5 to 300 s -1 and both upward and downward tests were performed in duplicate for each temperature and soluble solids content combination. The experimental procedure was previously tested by a rheological study of ethylene glycol and chlorobenzene (Telis-Romero et al, 2005;Polizelli et al, 2003).…”
Section: Density and Rheological Behaviormentioning
confidence: 99%
“…The empirical correlation for resistance coefficient K with Reynolds Number for non-Newtonian suspension flowing through local fittings is given by Eq. (11), which is suitable for different fittings [9][10][11][12]. The results for gradual contraction are listed in Table 2:…”
Section: Flow Of High Concentration Cws Through Gradual Contractionsmentioning
confidence: 99%
“…Many scholars have investigated the local resistance characteristics of different non-Newtonian fluids flowing through the sudden enlargements, sudden contractions, bends, valves and other parts of the local fittings, and have arrived at several empirical formulas [5][6][7][8][9]. Turian et al reported the resistance coefficient for laminar flow of non-Newtonian fluids was dependent on the size of different fittings [10].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the apparatus was checked using a CMC solution (1% w/w), which was pumped through the equipment at 68 different flow rates in the laminar range. At each flow rate, inlet and outlet temperatures in a straight pipe section of 1.80 m were measured with ten repetitions made at fiveminute intervals, in a procedure similar to that used by Polizelli et al (2003) and Telis-Romero et al (2005) when investigating friction losses in fittings during non-Newtonian fluid flow. The thermophysical properties of CMC solution were obtained from the work of Carezzato et al (2007).…”
Section: Experimental Apparatus For Determination Of the Bulk Temperamentioning
confidence: 99%